Association between Dietary behaviours and Dental Fluorosis- a Retrospective study - REZVI, FATHIMA BAREERA; P, DR. JESSY; CHAUDHARY, DR. MANJARI (The journal of contemporary issues in business and government, 2021)
Dental fluorosis is considered a major public health problem. Consumption of excess fluoride will lead to conditions like skeletal fluorosis and dental fluorosis. The aim of this study is to determine the association between dietary intake and fluorosis. The present study was conducted among patients who had reported to Saveetha Dental College, from the time period of June 2019 to March 2020. Case records of about 15,000 patients were reviewed and 561 patients were recruited who fulfilled the inclusion and exclusion criteria.Patients with dental fluorosis were included in the study. Patient age ,gender and the diet history and dean fluorosis index score were collected from the case records.Descriptive statistics, cross tabulation and chi-square test were done by SPSS IBM software 20.0. The results of the study showed that 49% of fluorosis patients are with a vegetarian diet and 51% of fluorosis patients are with a mixed diet. In patients with mixed diets the severity of fluorosis was slightly higher compared to vegetarian diet, with a Dean’s fluorosis index score of 4 - severe (5.3%). However it is statistically not significant. [Pearson’s Chi Square value: 4.685a df = 4, p value = 0.321 (>0.05)] Within the limits of the study no significant association was found between diet and fluorosis,however severity of fluorosis in mixed diet seems to be higher.